2015
DOI: 10.1093/cid/civ803
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Pneumococcal Disease Among Immunocompromised Persons: Implications for Vaccination Programs

Abstract: Immunocompromised individuals comprised 28% of IPD. Both PPV23 and herd immunity from pediatric PCV7 were associated with reductions in IPD in immunocompromised populations. PCV13 vaccination of immunocompromised adults may substantially reduce the residual burden until herd immunity from pediatric PCV13 is fully established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 40 publications
2
72
0
1
Order By: Relevance
“…pneumoniae is a Gram-positive coccus that can survive under both aerobic and anaerobic conditions [59]. It causes mucosal and invasive infections in children and adults, most commonly acute otitis media (AOM), community-acquired pneumonia (CAP), and invasive pneumococcal diseases (IPD), such as bacteraemia and meningitis [60][61][62][63][64].…”
Section: Pneumococcal Vaccinationmentioning
confidence: 99%
“…pneumoniae is a Gram-positive coccus that can survive under both aerobic and anaerobic conditions [59]. It causes mucosal and invasive infections in children and adults, most commonly acute otitis media (AOM), community-acquired pneumonia (CAP), and invasive pneumococcal diseases (IPD), such as bacteraemia and meningitis [60][61][62][63][64].…”
Section: Pneumococcal Vaccinationmentioning
confidence: 99%
“…Despite widespread vaccination, recent studies detected vaccine strains in up to 11% of individuals with community‐acquired invasive pneumococcal pneumonia, of which serotype 19A was most prevalent despite representation of this epitope in both PCV13 and PSV23 . The incidence of invasive pneumococcal disease in immunocompromised individuals is up to 20‐fold greater than in other adults with 50–64% of the isolates found among serotypes in PCV13; an additional 21% are caused by serotypes contained only in PSV23; some serotypes are in neither vaccine .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that adult and pediatric SOT recipients have greater IPD incidence than healthy children . Recently, population‐based surveillance has shown that patients who have received SOT or HSCT have a nearly 50‐fold increased incidence of IPD compared to the general population and a case‐fatality rate of 10%‐20% …”
Section: Pneumococcusmentioning
confidence: 86%